1998
DOI: 10.1074/jbc.273.14.8033
|View full text |Cite
|
Sign up to set email alerts
|

An Acyl-CoA Synthase (acoas) Gene Adjacent to the Mycocerosic Acid Synthase (mas) Locus Is Necessary for Mycocerosyl Lipid Synthesis in Mycobacterium tuberculosisvar. bovis BCG

Abstract: An open reading frame, ORF3, first identified adjacent to the mycocerosic acid synthase gene in Mycobacterium bovis BCG encodes a protein with acyl-CoA synthase (ACoAS) activity. Genes homologous to acoas are found adjacent to other multifunctional polyketide synthase genes in the mycobacterial genome. To test whether these gene products are necessary to esterify the fatty acids generated by the adjacent polyketide synthase gene products, the acoas gene was disrupted in M. bovis BCG using a suicide vector cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 27 publications
1
36
1
1
Order By: Relevance
“…Similarly, PapA5 homologs encoded in PDIM gene loci of other mycobacteria are expected to catalyze the diesterification required for synthesis of their PDIM variants. It had been suggested that FadD28, an acyl-CoA ligase encoded in the M. bovis PDIM gene locus and required for mycoside production, may catalyze phenol-POL diesterification or synthesize acyl-CoA precursors for MYC acid synthesis (17). In view of our results, and considering that FadD28 did not have AT activity in vitro (17), it is likely that FadD28 is required for the latter function.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Similarly, PapA5 homologs encoded in PDIM gene loci of other mycobacteria are expected to catalyze the diesterification required for synthesis of their PDIM variants. It had been suggested that FadD28, an acyl-CoA ligase encoded in the M. bovis PDIM gene locus and required for mycoside production, may catalyze phenol-POL diesterification or synthesize acyl-CoA precursors for MYC acid synthesis (17). In view of our results, and considering that FadD28 did not have AT activity in vitro (17), it is likely that FadD28 is required for the latter function.…”
Section: Discussioncontrasting
confidence: 38%
“…We selected PapA5, a suspected membrane-associated protein encoded in the Mt PDIM synthesis gene cluster (2,3,12,13,(16)(17)(18), as a representative Pap for functional characterization. Current models for PDIM synthesis propose involvement of at least three pks gene systems: (i) ppsA-E, required for POL and PONE synthesis (12); (ii) mas, required for mycocerosic (MYC) acid synthesis (12), and (iii) pks15͞1, required for incorporation of the phenolic group in mycoside PDIM variants (18).…”
mentioning
confidence: 99%
“…In contrast to conventional FAS, but similar to sFAS of Aspergillus (174,175), the products of MAS are not released from the enzyme but seem to be directly transferred to the long-chain diols phthiocerol and phenolphthiocerol (66,149). It is suggested that an open reading frame which is located in close proximity to the mas gene encodes an acyl-CoA ligase-like enzyme that may be implicated in this transesterification (42,66). Similar open reading frame adjacent to several other pks-and mas-like genes in the M. tuberculosis genome may exhibit corresponding functions.…”
Section: Fas-like Enzyme Systems In Mycobacteriamentioning
confidence: 99%
“…Apart from these structural differences, type I FASs may also be functionally differentiated on the basis of to various parameters which are discussed in more detail, below Furthermore, individual FASs may also differ by their specific cellular compartmentation being localized not only in the cytoplasm but also in organelles (16,145) and microsomal membranes (45,114). Occasionally, they are also found associated with subcellular structures, which subsequently serve as acceptors of their reaction products (39,40,42,166,174).…”
Section: Introductionmentioning
confidence: 99%
“…These lipids and their counterparts found in Mycobacterium leprae have been largely associated with pathogenicity (4 -9). Likewise, preliminary data indicate that p-HBADs, which are essentially recovered from the secretion products of the tubercle bacillus, modulate the secretion of pro-inflammatory cytokines by murine macrophages (10) and are required for virulence in immunodeficient mice (11).Because of the important roles played by PGL and p-HBADs in the pathogenesis of mycobacterial infections, their biosynthesis has stimulated some interest, and, during the last decade, several genes involved in the synthesis of the lipid core of PGL and in the methylation and glycosylation of PGL and p-HBADs have been described (3,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Most of these genes are clustered on a 70-kilobase region of the chromosome.…”
mentioning
confidence: 99%